Establishment of triple-negative breast cancer cells based on BMI: A novel model in the correlation between obesity and breast cancer - Shveid Gerson, Daniela; Gerson‐Cwilich, Raquel; Lara Torres, Cesar Octavio; Chousleb de Kalach, Alberto; Ventura Gallegos, José Luis; Badillo‐Garcia, Luis Ernesto; Bargalló Rocha, Juan Enrique; Maffuz‐Aziz, Antonio; Sánchez Forgach, Ernesto Roberto; Castorena Roji, Gerardo; Robles Vidal, Carlos D.; Vargas‐Castillo, Ariana; et al. (Frontiers in Oncology, 2022)
Obesity has been associated with an increased risk of more biologically aggressive variants in breast cancer. Women with obesity often have tumors diagnosed at later stages of the disease, associated with a poorer prognosis and a different response to treatment. Human cell lines have been derived from specific subtypes of breast cancer and have served to define the cell physiology of the corresponding breast cancer subtypes. There are no current cell lines for breast cancer previously derived from patients with different BMI nor specifically with an obese phenotype. The availability of those breast cancer cell lines will allow to describe and unravel functional alterations linked to these comorbidities. We established two different cell lines, DSG-BC1 and DSG-BC2, derived from a woman with ideal weight and obesity, respectively, both triple negative immune subtypes and performed a preliminary biological characterization. To our knowledge, these primary cultures are be the first in vitro representation where the influence of the comorbidly of breast cancer and obesity can be compared to breast cancer without overweight or obesity.